PENGARUH AKSES INFORMASI, DUKUNGAN SOSIAL, DAN LITERASI FISIK TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT: PERAN MODERASI SELF-EFFICACY - Irawan, Decky Candra; Suroto; Advendi Kristiyandaru (Universitas Negeri Medan, 2024)
This study analyzes the effect of information access, social support, and physical literacy on students' clean and healthy living behavior (PHBS), and tests the moderating role of self-efficacy. PHBS is an important foundation in shaping the character of healthy, productive, and competitive students. The study used a correlational quantitative approach with a cross-sectional design. Data were collected from 82 students of Dr. Soetomo Surabaya Junior High School through purposive sampling technique. The research instrument was a four-point Likert scale-based questionnaire that measured PHBS, information access, social support, physical literacy, and self-efficacy. Data analysis was conducted using Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results showed that social support and physical literacy had a significant influence on students' PHBS, while access to information was not significantly related. Self-efficacy was also not proven to moderate the relationship between independent variables and PHBS. This model explained 36.9% of the variance in students' PHBS, with dependence influenced by other factors. The findings emphasize the importance of social support and physical literacy in promoting PHBS, while information delivery strategies need to be improved to be more effective. Implications include school-based development programs involving families, teachers, and communities to improve physical literacy through extracurricular activities, supporting peer groups, and creating conducive physical and information environments. The findings are expected to be the basis for improving students' health and character building in a sustainable manner. Keywords: PHBS, Information Access, Social Support, Physical Literacy, Self-efficacy